2012
DOI: 10.1002/chir.22096
|View full text |Cite
|
Sign up to set email alerts
|

Viewing and Inducing Symmetry Breaking at the Single‐Molecule Limit

Abstract: Symmetry breaking by photons, electrons, and molecular interactions lies at the heart of many important problems as varied as the origin of homochiral life to enantioselective drug production. Herein we report a system in which symmetry breaking can be induced and measured in situ at the single-molecule level using scanning tunneling microscopy. We demonstrate that electrical excitation of a prochiral molecule on an achiral surface produces large enantiomeric excesses in the chiral adsorbed state of up to 39%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This set of DFT calculations also revealed that the barrier to inversion between the energetically equivalent enantiomers was 0.24 eV. This relatively high barrier was also evident with STM experiments, as the rotors were not observed to switch chirality under normal scanning conditions at either 5 or 78 K. Only by supplying high‐energy electrons (>0.4 eV) with the STM tip was it possible to overcome the high barrier to inversion and switch the chirality of the adsorbed molecules …”
Section: Creating Ratchet‐like Rotational Barriers By Tuning Moleculamentioning
confidence: 53%
See 4 more Smart Citations
“…This set of DFT calculations also revealed that the barrier to inversion between the energetically equivalent enantiomers was 0.24 eV. This relatively high barrier was also evident with STM experiments, as the rotors were not observed to switch chirality under normal scanning conditions at either 5 or 78 K. Only by supplying high‐energy electrons (>0.4 eV) with the STM tip was it possible to overcome the high barrier to inversion and switch the chirality of the adsorbed molecules …”
Section: Creating Ratchet‐like Rotational Barriers By Tuning Moleculamentioning
confidence: 53%
“…About 80% of all STM tips tested (both the etched W and cut Pt/Ir, the most commonly used STM probes) displayed this effect and hence are chiral. This result enabled us to differentiate between individual chiral molecules solely based on their apparent heights in STM . Perhaps most importantly we found that the tunneling electrons from a chiral tip have a stronger coupling to either right‐ or left‐handed molecules, resulting in rates of rotation of R and S rotors that differed by a factor of three under identical electrical excitation conditions .…”
Section: Regular Stm Tips Can Be Intrinsically Chiralmentioning
confidence: 76%
See 3 more Smart Citations